(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
This paper analyzes the curricular transformation in the Business Administration program with an emphasis on Production at the Universidad Estatal a Distancia (UNED), aiming to align academic training with labor market expectations and the competencies required by employers. Using a mixed-methods approach, semi-structured interviews were conducted with 17 operations experts and surveys were administered to 13 graduates, totaling 30 participants. The results indicate that 83% believe the current curriculum meets market needs, 90% highlight the importance of incorporating emerging technologies, and 76% feel that sufficient soft skills, such as effective communication and teamwork, are taught. These findings underscore the necessity for graduates to be familiar with digital tools, and collaboration with the business sector is crucial for enriching training and facilitating the transition to the labor market. In conclusion, curricular transformation should focus on a competency-based approach, integrating soft skills and emerging technologies, which will enhance graduates’ employability and ensure that training remains relevant.